Rangkuman surat keputusan Mahkamah Agung Republik Indonesia (SKMA-RI) dari tahun 1951 s.d. 1994. - Indonesia. Mahkamah Agung ([Jakarta] : Mahkamah Agung, Republik Indonesia, 1999)
Collection of letters of decisions of the Indonesian Supreme Court, 1951-1994.
Keywords: Law reports, digests, etc. -- Indonesia